ANALYSIS OF THE ROLE OF VILLAGE-OWNED ENTERPRISES (BUMDES) IN IMPROVING THE ECONOMY OF THE BONGKI LENGKESE VILLAGE COMMUNITY - Nisa, Marfuatu; Arifin, Zulkifli; Pasrah , Arham (Jurnal Ilmiah Administrasita', 2024)
This research focuses on the role of Village Owned Enterprises (BUMDes) in empowering the economy of the people of Bongki Lengkese Village. This research method uses a qualitative approach with the type of library research study. The data source comes from existing documents. The data analysis technique used is the interactive model analysis of Miles and Huberman, namely reducing data, presenting data, and drawing conclusions. The results of the study indicate that the role of BUMDes in empowering the economy of the people of Bongki Lengkese Village, namely, the role of BUMDes related to the service aspect of empowering the village community's economy, increasing village original income, the role of BUMDes related to aspects of increasing living standards has implications for growth and distribution of the rural economy.